Comparison of a New Miniaturized Extracorporeal Membrane Oxygenation System With Integrated Rotary Blood Pump to a Standard System in a Porcine Model of Acute Lung Injury. Issue 7 (4th December 2015) - Pilarczyk, Kevin; Heckmann, Jens; Lyskawa, Kathrin; Strauß, Andreas; Haake, Nils; Wiese, Ingo; Jakob, Heinz; Kamler, Markus; Pizanis, Nikolaus
Abstract: Extracorporeal membrane oxygenation (ECMO) is used for severe acute respiratory distress syndrome. However, available ECMO systems are large and not well designed for fast delivery, emergency implantation, and interhospital transfer. Therefore, a new miniaturized oxygenator with integrated rotary blood pump (ILIAS) was developed and compared with a standard ECMO system in a large animal model. Acute lung injury was induced with repeated pulmonary saline lavage in 14 pigs until PaO2 /FiO2 ‐ratio was <100 mm Hg with a positive‐end‐expiratory‐pressure of 5 mbar. Pigs were assigned to the following three groups: group 1 ( n = 4): control group with conventional ventilation; group 2 ( n = 5): standard vv‐ECMO; group 3 ( n = 5): vv‐ILIAS. Gas exchange, hemodynamics, hemolysis, and coagulation activation were examined over a period of 8 h. No device failed during the observation period. PaCO2 decreased from 59.40 ± 4.14 mm Hg to 48.62 ± 4.50 mm Hg after 1 h in the ILIAS group compared with an improvement of PaCO2 from 48.86 ± 7.45 to 40.10 ± 6.02 in the conventional ECMO group ( P = not significant [n.s.]). ARDS‐induced respiratory acidosis was controlled promptly with a pH of 7.2 ± 0.1 at baseline increasing to 7.4 ± 0.1 in both study groups after 60 min of ECMO support. Mean carbon dioxide transfer was comparable between the conventional ECMO and ILIAS (211.36 ± 78.39 mL/min vs. 219.99 ± 76.72 mL/min, P = n.s.). PaO2 /FiO2 increased from 118.4 ± 15.5 mm Hg to 179.1 ± 72.4 mm Hg in the ILIAS group compared with an improvement of oxygenation from 107.1 ± 24.9 mm Hg to 179.0 ± 45.7 mm Hg in the standard ECMO group ( P = n.s.). Mean oxygen transfer was calculated with 136.09 ± 30.25 mL/min for the ILIAS and 129.05 ± 36.28 mL/min for the standard ECMO. Hemodynamic instability or significant activation of the plasmatic coagulation was not observed. However, hemolysis was significantly higher in the ILIAS group compared with the conventional ECMO. As the ILIAS prototype provided excellent gas exchange with hemodynamic stability comparable with a standard ECMO system, we believe this study serves as a proof of concept. Further development and design modifications (optimized rotation speed and surface coating of rotor) are already done and another experiment is projected to reduce hemolysis and platelet consumption for clinical application.